PENGARUH PENGENDALIAN INTERNAL DAN MORALITAS INDIVIDU TERHADAP KECURANGAN AKUNTANSI PADA BADAN ASET DAN KEUANGAN DAERAH KABUPATEN TIMOR TENGAH UTARAG FRAUD IN THE REGIONAL ASSET AND FINANCE AGENCY OF TIMOR TENGAH UTARA DISTRICT - Redjo, Paulina Rosna Dewi; Aksa, Adi Faizal (Jurnal Akuntansi, 2025)
This study aims to analyze internal control (presence and absence) and individual morality (high and low) on the occurrence of fraud. The research method uses an experimental study on the Badan Aset dan Keuangan which has the obligation to organize accounting and accountability reports for the implementation of the Regional Budget. This research will combine the theory of fraud and ethics in the context of local government in Indonesia. Individual moral level (high and low) and organizational internal control elements (present and absent) are factors that will be investigated as causes of fraud. The fraud triangle theory and agency theory are the basis of this research. The results showed that individual morality and internal control were found to play an important role in preventing fraud.